PENGARUH KOMPOS LIMBAH KULIT NANGKA (Artocarpus heterophyllus) DENGAN METODE TAKAKURA TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN TOMAT CERI (Lycopesicum esculantum Mill) - Wisnu Rahmatullah; Yuni Krisnawati; Yunita Wardianti (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to determine the effect of jackfruit skin compost fertilizer (Artocarpus heterophyllus) with the takakura method on the growth and productivity of the cherry tomatoes (Lycopersicum esculentum Mill) plant. The study was conducted at the STKIP-PGRI Biology Garden in Lubuklinggau. Using a completely randomized design (CRD) with 6 treatments and 4 repetitions, namely P0 + (NPK), P0- (growing media), P1 (318 grams), P2 (381 grams), P3 (445 grams) and P4 (509 grams). The research parameters in the form of growth parameters include plant height and number of leaves, productivity parameters include the number of flowers, the number of fruit plants and the weight of fruit plants. Data collection techniques using observation sheets and analyzed with Anova. Compost fertilizer had no effect on the observation of plant height of Fe 1.83 <Ft 2.77, on observing the number of flowers Fe 0.43 <Ft 2.77, on observing the number of fruit Fe 2.21 <Ft 2.77. On the parameters of the number of leaves the data obtained were significant Fe 3.04> Ft 2.77, the weight of the data obtained was significant Fe 4.88> Ft 2.77. It can be concluded that jackfruit skin waste compost with takakura method has no effect on the height, number of flowers and the number of cherry tomato plants, but has an influence on the number of leaves and the weight of the fruit planted